Critical heat flux correlations for tube and annulus geometries under inclination and rolling conditions. (5th May 2023) - Kim, Geon-Woo; Yoo, Jin-Seong; Lee, Chang Won; Hong, Heepyo; Park, Goon-Cherl; Cho, Hyoung Kyu
Highlight: The CHF variation was expressed using two types of modified Froude numbers. Modified Froude number in DNB regime was revised to reduce inconsistency. Rolling attenuates the CHF variation through the inclination in any geometries. The correlation for rolling was also dependent on acceleration. Abstract: In floating nuclear reactors, critical heat flux (CHF) prediction is crucial because the CHF can be influenced under heaving, rolling, and inclination conditions, unlike in land-based reactors. Hence, the existing land-based empirical correlations of the CHF can be invalid under some conditions in marine reactors. Therefore, empirical correlations of the flow boiling CHF were developed in this study to predict the CHF under inclination and rolling motions in tubes and annuli. Available experimental CHF data (616 points) were collected including our previous experimental data (405 points) and their trends under marine conditions were analyzed. The CHF variation was expressed using two types of modified Froude numbers depending on the CHF regime—departure from nucleate boiling and dryout. These parameters were used in correlations for the CHF under inclination. CHF correlations under rolling conditions were developed. Rolling was found to attenuate the CHF variation through the inclination. This observation was reflected in the newly developed rolling CHF correlation. The proposed correlations adequately described the existing CHF experimental data under inclination and rolling within an uncertainty of 9.5%. The developed CHF correlations can be used for the safety analysis and reactor core thermal–hydraulic design of marine reactors.